2022
DOI: 10.3390/biology11060913
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Seasonal Changes in the Structure of Microbiome Inhabiting Bottom Sediments of a Pond Intended for Ecological King Carp Farming

Abstract: The main goal of the study was to determine changes in the bacterial structure in bottom sediments occurring over the seasons of the year and to estimate microbial metabolic activity. Bottom sediments were collected four times in the year (spring, summer, autumn, and winter) from 10 different measurement points in Cardinal Pond (Ślesin, NW Poland). The Next-Generation Sequencing (MiSeq Illumina) and Community-Level Physiological Profiling techniques were used for identification of the bacterial diversity struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Betaproteobacteria, the dominant proteobacteria in the catotelm of the studied fen profile, were a minor group in some bogs. However, they constituted the second largest group of proteobacteria in the rock underlying bogs (at a depth of 650-700 cm) [20] and were the most widespread class among proteobacteria in bottom sediments [53]. Among the cultivated representatives of Betaproteobacteria in the fen profile under study, bacteria of different genera with various functions were identified.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Betaproteobacteria, the dominant proteobacteria in the catotelm of the studied fen profile, were a minor group in some bogs. However, they constituted the second largest group of proteobacteria in the rock underlying bogs (at a depth of 650-700 cm) [20] and were the most widespread class among proteobacteria in bottom sediments [53]. Among the cultivated representatives of Betaproteobacteria in the fen profile under study, bacteria of different genera with various functions were identified.…”
Section: Discussionmentioning
confidence: 94%
“…Intermediate and rich fens, in contrast to bogs and poor fens, have an increased proportion of Bacteroidota [31]. Moreover, Bacteroidota, along with Proteobacteria and Acidobacteriota, was the main phyla in the microbiome of the bottom sediments [53]. In the studied fen profile, Bacteroidota was represented by the families Chitinophagaceae (35%-41%), Flavobacteriaceae (34%), or Cytophagaceae (35%) in the acrotelm and Sphingobacteriaceae (11%-36%), Chitinophagaceae (17%-28%), and env.OPS 17 (15%-27%) in the catotelm.…”
Section: Discussionmentioning
confidence: 99%